Prevalence and Demographic Differences in Work as a Calling in the United States: Results From a Nationally Representative Sample. (November 2021) - White, Micah J.; Marsh, Dylan R.; Dik, Bryan J.; Beseler, Cheryl L.
Within the last two decades, social science research on work as a calling has rapidly grown. To date, knowledge regarding prevalence and demographic differences of calling in the United States derives from data collected mainly from regionally limited and/or occupationally homogenous samples. The present study used data from the Portraits of American Life Study, a nationally stratified panel study of religion in the United States (U.S.), to estimate calling's prevalence in the U.S. Our findings represent the first known population estimates of seeking, perceiving, and living a calling in the U.S. Results revealed that calling is a relevant concept for many U.S. adults, with 43% endorsing "mostly true" or "totally true" to the statement "I have a calling to a particular kind of work." Small differences for presence of and search for a calling emerged across age groups, employment statuses, and levels of importance of God or spirituality. For living a calling, significant differences were identified only for importance of God or spirituality, contrasting with previous findings that suggested that living a calling varies as a function of income and social status. Implications for research and practice are explored.